Pilgrims in dialogue paths to interreligious encounter (Taiwan Kuangchi Program Service)
A documentary on three Asian communities that shows how people of different religions can live together harmoniously and work against poverty and for nature and peace.
Part I. Mountain of life (22 mins.) -- Part II. Dawn of truth (16 mins.) -- Part III. Chain of peace (26 mins.)
VHS.
Keywords: Seimeizan Community (Kyushu).; Satyodaya (Organization).; Silsilah Dialogue Institute; Religions -- Relations